Investigation of efficacy of asenapine on passive avoidance learning and memory and oxidative stress in animal model of seizure-induced with pentylenetetrazole - Farhadi, Elham; Mirazi, Naser; Hosseini, Abdolkarim (Acta Biologica Szegediensis, 2022)
Asenapine (ASE) has been used for treatment of bipolar disorder. There is also evidence that it may be useful in the treatment of neurodegenerative disorders. In this regard, the efficacy of ASE in an experimental model of seizure and memory impairment caused by seizures in rats has been investigated in the present study. Seizures in male Wistar rats (200-250 g) were induced by pentylenetetrazole (PTZ, 60 mg/kg, intraperitoneally (i.p.)), and the anticonvulsant effect of ASE (0.5 and 1 mg/kg, i.p.) was evaluated. The effect on memory was assessed using passive avoidance (PA) test in a shuttle box apparatus. After behavioral tests, the animals underwent deep anesthesia and were euthanized painlessly. Serum was isolated for oxidative stress assays (nitric oxide (NO), and glutathione (GSH)). Intraperitoneal injection of ASE decreased the mean number of myoclonic jerks and duration of generalized tonic clonic seizures (GTCS) and increased the mean latency of myoclonic jerk and GTCS compared to the PTZ group. Moreover, in the PA test, ASE caused a significant increase in retention latency (RL) and total time spent in the light compartment (TLC) compared to the PTZ group. Biochemical tests showed that ASE was able to significantly increase GSH serum levels and significantly reduce NO serum levels compared to the PTZ group. Overall, this study suggests the potential neuroprotective effects of ASE in a model of memory impairment caused by seizures via the mechanism of inhibition of the oxidative stress pathway.